Właściwości fizyczno-chemiczne gleb terenu przemysłu metalowego - Fruzińska, Róża (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the paper have been described the chosen physicochemical properties of soil: dry residues after incineration, pH in H2O and KCl, hydrolytic acidity (Hh), base content (S), soil capacity of the exchangeable cations (T), base saturation (V), electric conductivity (EC). Soils from the industrial area showed abnormal results of analyzed properties, different from the typical values for urban soils. Impurities of the soils surface layer (0-20 cm) has been caused by industrial activity and rubble and slages deposition.
Keywords: przemysł metalowy; gleba; zanieczyszczenia; domieszki antropogeniczne; "Bazany" forest reserve; soil pollution; anthropogenic dope